2018
DOI: 10.1016/j.rse.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Short-lived ice speed-up and plume water flow captured by a VTOL UAV give insights into subglacial hydrological system of Bowdoin Glacier

Abstract: The subglacial hydrology of tidewater glaciers is a key but poorly understood component of the complex ice-ocean system, which aects sea level rise. As it is extremely dicult to access the interior of a glacier, our knowledge relies mostly on the observation of input variables such as air temperature, and output variables such as the ice ow velocities reecting the englacial water pressure, and the dynamics of plumes reecting the discharge of meltwater into the ocean. In this study we use a cost-eective Vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 49 publications
3
62
0
Order By: Relevance
“…The case studies of a calving front and ice sheet interior provided in this study show two different applications of the GNSS-AT method: one in a calving front environment where UAVs have previously been used, and one in an ice sheet interior, where UAVs have not to date been used to assess ice dynamics. The first case study highlights that existing observations 10 of, for instance, calving events (Ryan et al, 2015;Jouvet et al, 2017Jouvet et al, , 2018 can be successfully replicated using GNSS-AT methods (Fig. 5).…”
Section: Applicationsmentioning
confidence: 84%
See 3 more Smart Citations
“…The case studies of a calving front and ice sheet interior provided in this study show two different applications of the GNSS-AT method: one in a calving front environment where UAVs have previously been used, and one in an ice sheet interior, where UAVs have not to date been used to assess ice dynamics. The first case study highlights that existing observations 10 of, for instance, calving events (Ryan et al, 2015;Jouvet et al, 2017Jouvet et al, , 2018 can be successfully replicated using GNSS-AT methods (Fig. 5).…”
Section: Applicationsmentioning
confidence: 84%
“…However, it has been shown that the error of a GNSS-AT-derived product can be further constrained by the reintroduction of at least one GCP, with a final vertical accuracy only slightly worse than traditional GCP networks (Benassi et al, 2017). Whilst constructing a comprehensive network of GCPs might be difficult on glacial terrain, the introduction of one 15 GCP, either in the form of an existing continuous GPS station, or a single target measured on a per-flight basis or interpolated linearly as per Jouvet et al (2017Jouvet et al ( , 2018, is far more achievable than a large, dense network of GCPs. The method as described here also lacks the incorporation of directional data in the camera coordinate positions, and hence is referred to as GNSS-AT rather than full DSO (section 2.3).…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…• tidal driven variability of the ice flow of ocean-terminating glaciers (Sugiyama et al, 2015) or the tidal flexure of ice shelves, which be can used to locate the grounding line (Le Meur et al, 2014), • short-lived speed-up events caused by a abrupt change in the subglacial hydrological system (e.g., Jouvet et al, 2018), • fracturing processes, such as small-scale calving (Walter et al, 2019) or the rifting of a tabular icebergs (Joughin and MacAyeal, 2005;Bassis and Jacobs, 2013;Medrzycka et al, 2016).…”
Section: Discussionmentioning
confidence: 99%